Epigenetic Reprogramming During Somatic Cell Nuclear Transfer: Recent Progress and Future Directions - Wang, Xiangyu; Qu, Jiadan; Li, Jie; He, Hongbin; Liu, Zhonghua; Huan, Yanjun (Frontiers in Genetics, 2020)
Somatic cell nuclear transfer (SCNT) has broad applications but is limited by low cloning efficiency. In this review, we mainly focus on SCNT mediated epigenetic reprogramming in livestock and also describe mice data for reference. This review presents the factors contributing to low cloning efficiency, demonstrates that incomplete epigenetic reprogramming leads to the low developmental potential of cloned embryos, and further describes the regulation of epigenetic reprogramming by long noncoding RNAs, which is a new research perspective in the field of SCNT-mediated epigenetic reprogramming. In conclusion, this review provides new insights into the epigenetic regulatory mechanism during SCNT-mediated nuclear reprogramming, which could have great implications for improving cloning efficiency.